1999
DOI: 10.1063/1.123511
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity investigation of the electron dynamics in GaAs grown at low temperature

Abstract: We present detailed measurements of photoconductivity as functions of illumination power and temperature on metal–semiconductor–metal photodetectors made of low-temperature GaAs grown at different temperatures (225–350 °C). The extracted carrier lifetimes show the expected dependence as a function of growth temperature. Additionally, our experiments show an order-of-magnitude variation of the extracted lifetimes as functions of measurement temperature and illumination intensity. We propose a simple model based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…6, 21 We should note that doing this, we assumed that the defects were the same for all samples ͑annealed or not͒. 23 the deep-donor absorption cross section is fixed at DD =2ϫ 10 −16 cm 2 ͑which gives ␣ DD =5ϫ 10 3 cm −1 for N DD = 2.5ϫ 10 19 cm −3 ͒, and we have determined a unique best set of electron and hole crosssections ͑ n and p ͒ for all samples.…”
Section: Fitting Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…6, 21 We should note that doing this, we assumed that the defects were the same for all samples ͑annealed or not͒. 23 the deep-donor absorption cross section is fixed at DD =2ϫ 10 −16 cm 2 ͑which gives ␣ DD =5ϫ 10 3 cm −1 for N DD = 2.5ϫ 10 19 cm −3 ͒, and we have determined a unique best set of electron and hole crosssections ͑ n and p ͒ for all samples.…”
Section: Fitting Methodologymentioning
confidence: 99%
“…21,22 The rate equations concern an electron density in the conduction band n, a hole density in the valence band p, and a nonionized deep-donor density n DD . 21,22 The rate equations concern an electron density in the conduction band n, a hole density in the valence band p, and a nonionized deep-donor density n DD .…”
Section: A Hole and Electron Density Calculationmentioning
confidence: 99%
“…͑8͒, (1) is the first order susceptibility associated with a constant index of refraction n or constant absorption coefficient. The second order susceptibility (2) is associated with second harmonic generation, which is not significant in our material.…”
Section: A Background and Motivationmentioning
confidence: 99%
“…3 They found that the relationship predicted by Ruda and Shik was applicable. 4 As for excess As point defects, a number of studies have analyzed relaxation processes on the basis of rate equations, [5][6][7][8] but no study has reported a dependence of the carrier lifetime on experimentally determined concentrations of excess As point defects in LT-GaAs or LT-MQW. Only the dependence of the carrier lifetime on the growth temperature [9][10][11][12][13][14][15] or the flux conditions 16 has been investigated, and hence, its dependence on the excess As concentrations has been only qualitatively discussed to date.…”
Section: Introductionmentioning
confidence: 99%